2009
DOI: 10.1210/jc.2008-1441
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Inpatient Insulin Regimens with Detemir plus Aspart Versus Neutral Protamine Hagedorn plus Regular in Medical Patients with Type 2 Diabetes

Abstract: Treatment with basal/bolus regimen with detemir once daily and aspart before meals results in equivalent glycemic control and no differences in the frequency of hypoglycemia compared to a split-mixed regimen of NPH and regular insulin in patients with type 2 diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
122
3
4

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 148 publications
(137 citation statements)
references
References 38 publications
7
122
3
4
Order By: Relevance
“…A study of inpatients with diabetes in the UK found that 22% had one or more hypoglycaemic episodes over the previous 7 days of their stay (blood glucose measurement of 70 mg/ dl (3.9 mmol/l) or less) [52]. In the USA, the reported prevalence of hypoglycaemia in inpatients is from 3 to 29% [53][54][55][56]. The risk factors for developing inpatient hypoglycemia include older age, presence of comorbidities, diabetes, increasing number of antidiabetic agents, tight glycaemic control, septic shock, renal insufficiency, mechanical ventilation, and severity of illness [57,58].…”
Section: Hypoglycaemia and Outcomesmentioning
confidence: 99%
“…A study of inpatients with diabetes in the UK found that 22% had one or more hypoglycaemic episodes over the previous 7 days of their stay (blood glucose measurement of 70 mg/ dl (3.9 mmol/l) or less) [52]. In the USA, the reported prevalence of hypoglycaemia in inpatients is from 3 to 29% [53][54][55][56]. The risk factors for developing inpatient hypoglycemia include older age, presence of comorbidities, diabetes, increasing number of antidiabetic agents, tight glycaemic control, septic shock, renal insufficiency, mechanical ventilation, and severity of illness [57,58].…”
Section: Hypoglycaemia and Outcomesmentioning
confidence: 99%
“…The prevalence of hypoglycemia in critically ill patients ranged between 5% and 28%, [18] and in noncritical care settings between 1% and 33%. [19] The most common risk factors are older age, change in nutritional intake (reduced oral intake, emesis, unexpected interruption of enteral or parenteral feedings), inappropriate administration of short-acting insulin's relation to meals and failure to adjust treatment when we reduce the infusion rate of intravenous dextrose or steroid therapy. [20,21] Hypoglycemia in hospitalized T2DM patients has been associated with poor outcomes and 2.8 days longer hospital stay.…”
Section: Treatment Of Hypoglycemiamentioning
confidence: 99%
“…Correction or supplemental insulin aims to control existing excessive hyperglycemia. The use of insulin regimens that consider these components is an effective strategy to control hyperglycemia and to maintain euglycemia in hospitalized noncritically ill patients [11, 25,26]. Correction or supplemental insulin should be distinguished from sliding scale insulin, which refers to insulin administered as monotherapy on an 'as needed' basis in an attempt to treat hyperglycemia after it occurs.…”
Section: Management Of Hyperglycemia In the Medical And Surgical Wardsmentioning
confidence: 99%